EEG correlates of awareness of vocal errors in self-produced speech - Suchy, Daniel (My University, 2023)
Background: Previously published results suggest that participants correct for errors in self-produced speech without conscious control. When participants are exposed to auditory feedback modified with artificial pitch alterations, they adapt the pitch of their own voice to compensate for the presented pitch shift. This happens even if the pitch shift is so low, that the participants are often unaware of its presence. Our goal is to measure the effect of awareness on vocal control when healthy participants are exposed to perception-threshold-level pitch alterations. Methods: Participants vocalized simple speech sounds and were presented with real-time low-magnitude pitch shifts, which were calibrated to individual perceptional abilities. We asked the participants if they were aware of the pitch shift and measured vocal and electrophysiological (event-related potentials) responses to it. Results: Participants were significantly more likely to compensate for the pitch shift if they were aware of it. Unaware trials did not lead to higher chance of compensation, compared to trials without pitch shift. Awareness did not have a significant effect on the magnitude of electrophysiological responses to the pitch shift. Conclusions: Unaware pitch adaptations were not observed in a paradigm that adjusts the task difficulty to individual perceptional abilities. No evidence was found for the existence of separate aware and unaware processing of self-produced speech sounds by the brain. Significance: Our experiment is the first to measure the effects of awareness on vocal control when the pitch shift is calibrated to individual perceptional abilities. Our experiment is also the first to measure the neural correlates of awareness of self-produced sounds.
Keywords: speech perception, auditory feedback, event-related potentials, auditory awareness negativity, late positivity, perception-action disassociation, subliminal perception